Arrhythmias following Revascularization Procedures in the Course of Acute Myocardial Infarction: Are They Indicators of Reperfusion or Ongoing Ischemia? - Tatli, Ersan; Alicik, Guray; Buturak, Ali; Yilmaztepe, Mustafa; Aktoz, Meryem (HINDAWI LTD, 2013)
Objective. The most important step in the treatment of ST elevation myocardial infarction is to sustain myocardial blood supply as soon as possible. The two main treatment methods used today to provide myocardial reperfusion are thrombolytic therapy and percutaneous coronary intervention. In our study, reperfusion arrhythmias were investigated as if they are indicators of coronary artery patency or ongoing ischemia after revascularization. Methods. 151 patients with a diagnosis of acute ST elevation myocardial infarction were investigated. 54 patients underwent primary percutaneous coronary intervention and 97 patients were treated with thrombolytic therapy. The frequency of reperfusion arrythmias following revascularization procedures in the first 48 hours after admission was examined. The relation between reperfusion arrhythmias, ST segment regression, coronary artery patency, and infarct related artery documented by angiography were analyzed. Results. There was no statistically significant difference between the two groups in the frequency of reperfusion arrhythmias (P = 0.355). Although angiographic vessel patency was higher in patients undergoing percutaneous coronary intervention, there was no significant difference between the patency rates of each group with and without reperfusion arrythmias. Conclusion. Our study suggests that recorded arrhythmias following different revascularization procedures in acute ST elevation myocardial infarction may not always indicate vessel patency and reperfusion. Ongoing vascular occlusion and ischemia may lead to various arrhythmias which may not be distinguished from reperfusion arrhythmias.